Empowering church leaders for service in Africa: Situational Holistic Pastoral Ministry paradigm - Rabson Hove (In die Skriflig)
Empowering church leaders globally is a contested terrain, particularly in Africa. This article explores the challenges and pitfalls of church leadership on the continent. It not only examines the complexities of contemporary African church leadership but also proposes strategies for modelling its transformative development. The focus is on critically assessing how church leaders can be empowered to transform both the church and communities in Africa through the Situational Holistic Pastoral Ministry (SHPM) paradigm. The article argues that numerous challenges in Africa can be mitigated by equipping church leaders for transformative roles. A key issue identified is the tendency to idolise clergy, placing them at the centre of ministry, rather than fostering their role as models who empower others. Drawing on insights from SHPM theory, this article evaluates the empowerment of church leaders for transformative action within the African context. It concludes by emphasising the need to empower church leaders to facilitate the transformation of both the church and its surrounding communities.